Hubungan Koping Perawat dan Kecerdasan Emosional terhadap Perilaku Caring - Prihandhani, IGAA Sherlyna; Trisna, Made Oktaviani Bulan; Widistuti, Putu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between coping and emotional intelligence of nurses toward caring behavior at Garba Med Hospital Kerobokan. This research method uses a quantitative method with a cross-sectional design. The results of the multivariate test show that each variable has a significance value <0.005. In conclusion, there is a relationship between nurse coping and emotional intelligence towards caring behavior at Garba Med Hospital Kerobokan. Keywords: Caring, Emotional Intelligence, Nurse Coping